Wavelength-tuning multiple-surface interferometric analysis with compression of Zernike piston phase error. (November 2021) - Seo, Jiwon; Kim, Yangjin; Bae, Wonjun; Moon, Young Hoon; Sugita, Naohiko
Highlights: Formulation of Zernike piston phase error. Development of 6 N  – 3 algorithm that can eliminate Zernike piston phase error. Numerical error analysis of 6 N  – 3 algorithm with comparisons to other algorithms. Measurement of thickness homogeneity and surface profile of glass plate. Abstract: In this study, we propose a 6 N  – 3 algorithm for suppressing the Zernike piston phase error by expanding 6 N  – 5 algorithm using algorithmic polynomial theory. We demonstrate that the proposed algorithm can be used for simultaneous measurement of the surface profile and thickness homogeneity by rotating the characteristic diagram on the complex plane. We applied Fourier analysis to confirm the properties of 6 N  – 3 algorithm in the frequency domain. We then estimate the error-compensating capability of 6 N  – 3 algorithm, after which we compare this capability to that of classical algorithms using numerical error analysis. To verify the effectiveness, we conducted an experiment using 6 N  – 3 algorithm and Fizeau interferometer to measure the thickness homogeneity and surface profile of a glass plate. The standard deviation of the measured thickness homogeneity was 1.965 nm, which was significantly smaller than that of the other classical algorithms.